G78(P) Female genital mutilation (FGM) surveillance in under 16 years olds in the UK and Ireland. (24th May 2017) - Hodes, D; Pall, K; O'Donnell, N Ayadi; Lynn, R; Armitage, A; Creighton, S; Debelle, G; Viner, R
Abstract : Aims: This study aims to describe the presentation, incidence and clinical management of children with FGM in the UK and Ireland. Methods: Cases of FGM are reported using the established British Paediatric Surveillance Unit (BPSU) orange card system. The online data collection period is from November 2015–November 2016. The sexual referral centres (SARCS) have agreed to participate. The study also includes a 12 month follow up. Results: Of the 55 cases reported to the BPSU, 29 (53%) had confirmed FGM of which we are awaiting outstanding information, 20 were reported in error, or were duplicates, six questionnaires are incomplete. The results presented are interim findings on the 29. Of the completed questionnaire items, at the time of diagnosis all children were older than four years (n=26), most children were diagnosed at 4–6 years (n=7) or 13–16 years (n=7), followed by 7–9 years (n=6) and 10–12 years (n=6). Almost all children were born outside of the UK, in African countries (n=25). For confidentiality purposes we cannot disclose the place of birth for those children born outside of African countries (n=2), the place of birth was unknown for two cases. Social care referred most children (66%, n=19), and health professionals the remainder (34%, n=10) with a history of FGM (83%, n=26) or suspected FGM (n=<5). No children presented with a history of labioplasty or genital piercing. The circumstances of FGM were known in 19 cases of which 7 (32%) were performed by a healthcare professional either in a family members house/village (n=5) or clinic (n=2). Conclusion: The first year of reporting has shown that cases are being found and investigated. The reporting of clinical presentation and examination findings can be used to educate healthcare professionals and plan health services. The study extension will help to identify the true incidence, presentation and management of cases.